2017
DOI: 10.1007/s00262-017-2042-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel prostate cancer immunotherapy with a DNA-encoded anti-prostate-specific membrane antigen monoclonal antibody

Abstract: Prostate-specific membrane antigen (PSMA) is expressed at high levels on malignant prostate cells and is likely an important therapeutic target for the treatment of prostate carcinoma. Current immunotherapy approaches to target PSMA include peptide, cell, vector or DNA-based vaccines as well as passive administration of PSMA-specific monoclonal antibodies (mAb). Conventional mAb immunotherapy has numerous logistical and practical limitations, including high production costs and a requirement for frequent dosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…We next examined the in vivo activity and stability of ACE-tRNA. We delivered the NLuc-UGA PTC reporter cDNA together with a plasmid encoding four copies of the ACE-tRNA Arg UGA or an ‘empty vector control’ into mouse skeletal muscle (tibialis anterior) using electroporation 40-42 . We then compared these data to the expression of the WT NLuc.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the in vivo activity and stability of ACE-tRNA. We delivered the NLuc-UGA PTC reporter cDNA together with a plasmid encoding four copies of the ACE-tRNA Arg UGA or an ‘empty vector control’ into mouse skeletal muscle (tibialis anterior) using electroporation 40-42 . We then compared these data to the expression of the WT NLuc.…”
Section: Resultsmentioning
confidence: 99%
“…Muthumani et al were the first to demonstrate a novel DMAb approach to target cancer, developing an anti-prostate-specific membrane antigen (anti-PSMA) encoded DNA in a mouse prostate cancer model [116]. In vivo, their study showed expression for this DMAb delivery of over 105 days post-injection, with important anti-tumor functionality, as tumor-challenged mice exhibited tumor regression and greater than 80% survival 58 days post-challenge compared to 0% survival in the vector control mice.…”
Section: Cancer Immunotherapymentioning
confidence: 99%
“…Although, engineered viruses are nowadays a prevalent gene delivery method, plasmids encoding cDNAs can also be directly electroporated in vivo [39]. For instance, the electroporation of a plasmid encoding an antibody directed against PSMA (prostate specific membrane antigen), a TAA associated to prostate cancer, led to the production of transgenic antibodies in vivo [39].…”
Section: General Notions Of Vector Designmentioning
confidence: 99%